2015
DOI: 10.3390/ijms160818865
|View full text |Cite
|
Sign up to set email alerts
|

Major Alterations of Phosphatidylcholine and Lysophosphotidylcholine Lipids in the Substantia Nigra Using an Early Stage Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disease affecting the nigrostriatal pathway, where patients do not manifest motor symptoms until >50% of neurons are lost. Thus, it is of great importance to determine early neuronal changes that may contribute to disease progression. Recent attention has focused on lipids and their role in pro- and anti-apoptotic processes. However, information regarding the lipid alterations in animal models of PD is lacking. In this study, we utilized high performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…PD, as other neurodegenerative diseases, is also recognized to have an inflammatory component, yet poorly understood (Qin et al, ). In agreement with these findings, the lipid analysis of the substantia nigra region of an early‐stage rat model of PD has revealed the up‐regulation of the same LPC species, which are considered crucial for neuroinflammatory signaling (Farmer, Smith, Hayley, & Smith, ).…”
Section: Discussionmentioning
confidence: 59%
“…PD, as other neurodegenerative diseases, is also recognized to have an inflammatory component, yet poorly understood (Qin et al, ). In agreement with these findings, the lipid analysis of the substantia nigra region of an early‐stage rat model of PD has revealed the up‐regulation of the same LPC species, which are considered crucial for neuroinflammatory signaling (Farmer, Smith, Hayley, & Smith, ).…”
Section: Discussionmentioning
confidence: 59%
“…33 Another investigation of 6hydroxydopamine-treated rats found that the substantia nigra underwent marked alterations of lipid metabolism, including either downregulation or upregulation for the synthesis of several phosphatidylcholine and lysophosphotidylcholine lipid species. 34 To date, no other biospecimen marker studies have offered correlations as strong as that found for the prediction of change in the clinical measures of PD progression used in this study, which, in our participants, increased by z47% over a mean of 11 months. Our untargeted approach resulted in the discovery of some biomarkers not previously recognized as involved in PD neurodegeneration.…”
mentioning
confidence: 48%
“…ATP10B dysfunction also diminishes lysosomal PC export, which may further contribute to the disease mechanism. Indeed, the PC lipid composition was shown to be disturbed in the substantia nigra of a PD rat model treated with 6-hydroxydopamine [36]. Moreover, loss of function mutations in PLA2G6, encoding a phospholipase involved in repair of oxidative damage to membrane phospholipids, membrane remodeling and iron homeostasis, are also shown to affect neuronal lipid homeostasis [14,83,98].…”
Section: Discussionmentioning
confidence: 99%